Asymmetric Brønsted Acid Catalyzed Cycloadditions of ortho-Quinone Methides and Related Compounds - Dorsch, Caroline; Schneider, Christoph (Synthesis, 2022)
This review summarizes recent developments in the area of Brønsted acid catalyzed, enantioselective cycloadditions of ortho-quinone methides, ortho-quinone methide imines as well as heterocyclic indole- and pyrrole-based methides. In a straightforward and single-step transformation complex polycyclic N- and O-heterocyclic scaffolds are accessible, with typically good yields and excellent stereocontrol, from simple benzyl and heterobenzyl alcohols upon acid-catalyzed dehydration. The transient precursors are hydrogen-bonded to a chiral Brønsted acid which controls the enantioselectivity of the process.1 Introduction2 Cycloadditions of ortho-Quinone Methides2.1 Brønsted Acid Catalyzed Processes2.2 Cooperative Brønsted Acid/Transition-Metal-Catalyzed Processes3 Cycloadditions of ortho-Quinone Methide Imines4 Cycloadditions of Indolyl-3-methides5 Cycloadditions of Indolyl-2-methides5.1 Brønsted Acid Catalyzed Processes5.2 Cooperative Brønsted Acid/Transition-Metal-Catalyzed Processes6 Cycloadditions of Pyrrolyl-2-methides7 Cycloadditions of Pyrrolyl-3-methides8 Conclusions
Keywords: cycloaddition; heterocycles; indoles; pyrroles; chromans; enantioselectivity; Brønsted acid catalysis